“Everything has to be done in the Polish way”: creativity barriers experienced by innovators in a post-Soviet society - Karpinska, Agnieszka (Creativity Studies, 2024)
Innovators from post-Soviet transition societies experience barriers to creativity different from those experienced by inventors in developed countries. Since there has been little research into this subject so far, this article is an attempt to fill this gap. The aim of the study is to explore the mindset and environmental creativity hurdles experienced by Polish innovators as the representatives of post-Soviet states. The data was collected through individual in-depth interviews. Sixteen innovators from Białystok, a city in the Eastern part of Poland, were interviewed. The findings show that innovators experience both individual and environmental hurdles in their creativity actions. In the case of mindset barriers, the feeling of low self-esteem and lack of appropriate knowledge are listed as the most significant barriers, especially at the beginning of the career. The study has shown that although individual barriers hinder creative work, innovators make successful attempts to overcome them. Environmental blocks, however, have the most detrimental influence on innovators’ creativity and are the most difficult to overcome. Among these barriers innovators mention the characteristics of homo sovieticus mentality, such as informal relations, nepotism, and lack of trust among academics and businesspeople. The study supports the hypothesis that the post-Soviet culture largely determines the low innovation level in Eastern European countries.